PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAN HASIL PERTANIAN UBI JALAR DI DESA SELOTAPAK - Asmawati, Endah; Herlambang, Arif (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2020)
Selotapak is one of the villages in the Trawas District area of ​​Mojokerto Regency, East Java. This village is one of the sweet potato producing communities. At the time of harvest, the harvest reaches 40-50 tons per hectare. But often at the time of harvest, the price of sweet potatoes becomes very low. This price makes farmers unable to benefit, even many who lose. On the other hand, the storage period of sweet potatoes is also not long. The farmers must immediately sell their crops. Therefore another alternative is needed in marketing sweet potatoes so that the selling price can increase. One way to do this is by processing sweet potatoes into other products with longer shelf life and higher prices. In this activity, training in preparing sweet potatoes into several products, namely flour, noodles, brownies, roll ice cream, and yoghurt. This activity can be done through PKK empowermen and several youth organizations. Based on the training results, over 80% of the training participants feel the benefits of the training,. The participants can practice it independently in producing this sweet potato-based product. By making sweet potatoes into flour, the storage period extended. Sweet potato flour can be used to make other food products that become superior products in the village of Selotapak. For the sustainability of sweet potato processing, it is necessary to cooperate with all village communities in marketing their products. The role of the village government is essential in this regard, for example, by requiring presenting sweet potato products (at least one piece) as consumption in each village activity. For the next steps, supporting training is needed for the development of superior village products, for example training in making packaging and marketing.